2012
DOI: 10.1021/ja203465y
|View full text |Cite
|
Sign up to set email alerts
|

EPR–ENDOR Characterization of (17O, 1H, 2H) Water in Manganese Catalase and Its Relevance to the Oxygen-Evolving Complex of Photosystem II

Abstract: The synthesis of efficient water-oxidation catalysts demands insight into the only known, naturally occurring water-oxidation catalyst, the oxygen-evolving complex (OEC) of photosystem II (PSII). Understanding the water oxidation mechanism requires knowledge of where and when substrate water binds to the OEC. Mn catalase in its Mn(III)-Mn(IV) state is a protein model of the OEC’s S2 state. From 17O-labeled water exchanged into the di-μ-oxo di-Mn(III,IV) coordination sphere of Mn catalase, CW Q-band ENDOR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
121
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(143 citation statements)
references
References 72 publications
19
121
2
Order By: Relevance
“…(vi) The assignments generally agree with comparisons with model systems [25,45,46]. (vii) The exchange rates are typically considered too fast for the existence of an m-oxo bridge, based on comparison with model complex data [45,46] and catalase data [25]. [47,48] and the displacement of NH 3 by W1 and O5 was assigned as the exchangeable bridge [49], the results showed that all 'waters', including the moxo bridge, were exchanged within 15 s. It can be concluded that all exchangeable sites could serve as a bound substrate in the S 1 state.…”
Section: Stromasupporting
confidence: 65%
See 3 more Smart Citations
“…(vi) The assignments generally agree with comparisons with model systems [25,45,46]. (vii) The exchange rates are typically considered too fast for the existence of an m-oxo bridge, based on comparison with model complex data [45,46] and catalase data [25]. [47,48] and the displacement of NH 3 by W1 and O5 was assigned as the exchangeable bridge [49], the results showed that all 'waters', including the moxo bridge, were exchanged within 15 s. It can be concluded that all exchangeable sites could serve as a bound substrate in the S 1 state.…”
Section: Stromasupporting
confidence: 65%
“…(v) The slow exchange rate is also perturbed by Ca/Sr exchange [44]. (vi) The assignments generally agree with comparisons with model systems [25,45,46]. (vii) The exchange rates are typically considered too fast for the existence of an m-oxo bridge, based on comparison with model complex data [45,46] and catalase data [25].…”
Section: Stromamentioning
confidence: 55%
See 2 more Smart Citations
“…An experimental 17 O isotropic hfc of magnitude 1.5 or 3.8 MHz was recently measured for the water oxygen. 13,26 Spin projected 17 O isotropic hfcs for models A, A(OH), and B are shown in Table 3. A comparison of the calculated results for the three model systems with the experimental value strongly supports either model A or model A(OH).…”
mentioning
confidence: 99%